Experiment and Mechanism Investigation on Freezing-Thawing of Sandstone with Different Water Contents. (15th November 2021) - Song, Guilei; Chen, Longxiao; Li, Kesheng; Zhang, Deng; Xu, Junhao; Xu, Wenshuo; Liu, Chuanxiao; Zhang, Jinpeng
Abstract : Freezing-thawing cycles seriously affect the safety of underground engineering in cold regions. At present, most research studies focus on the effect of number and freezing temperature on freezing-thawing cycles. As another important factor, the mechanism of rock mass water content affecting freezing-thawing is less studied. This paper studied the influence of the water content on mechanical property, microstructure, and acoustic emission characteristics of sandstone. The results indicated that the uniaxial compressive strength (UCS) and elastic modulus ( E ) of sandstone after 20 freezing-thawing cycles decreased as the water content increased. However, the decreasing rate of UCS gradually decreased, while the decreasing rate of E gradually increased. Furthermore, the empirical formulas of UCS and E about water content were obtained. The porosity and plasticity of sandstone after 20 freezing-thawing cycles increased as the water content increased. The empirical formulas of UCS and E about water content were obtained. The porosity and plasticity of sandstone after 20 freezing-thawing cycles increased as the water content increased. The decreasing trend of UCS with porosity was the same as that of UCS with water content. The failure form of sandstone gradually changed from splitting failure to shear failure. The results of the acoustic emission test showed that the stress-strain curves combined with acoustic emission ring counting could reveal the damage evolution process of sandstone during loading.